Ages of detrital zircons from deep-water gas field L3 in the Northern South China Sea and their significance for provenance evolution - Liu, Zhenghua; Goh, Thian Lai; Abdul G.M. Rafek; Ailie S. Serasa; Lee, Khai Ern (Penerbit Universiti Kebangsaan Malaysia, 2025)
L3 is the first deepwater exploration well drilled in the Pearl River Mouth Basin, Northern South China Sea and significant hydrocarbon discoveries have been discovered in the Zhuhai and Zhujiang Formations, which have kicked off the prelude to oil and gas exploration in the deepwater areas of the northern slope of the South China Sea (SCS). However, for a long time, there has been great controversy over the cause, sedimentation on processes and control factors of high-quality reservoirs in L3 gas field. This paper analyzed the sedimentary characteristics of the high-quality sand bodies of Zhuhai Formation and Zhujiang Formation, combined with a comprehensive analysis of detrital zircon U-Pb age spectra patterns of sediments and conducted a source-to-sink comparative analysis based on the detrital zircon U-Pb age spectrum in the surrounding potential source areas. The results show that the shallow sea delta developed since the late Oligocene in L3 gas field, and the age spectrum of sedimentary zircon showed the characteristics of multi-peaking, which was the signal superposition of western paleo ‘Kontum-Ying-Qiong’ River and northern paleo Pearl River. Jinningian zircon spectrum peak shows an increasing trend as the sand body was gradually deposited, which indicated that the supply of paleo Pearl River in the north was gradually increasing. After the Baiyun movement at the end of the Oligocene, with the deepening of the water body, the dominant sand body of L3 in the Zhujiang Formation showed significant deep-water sedimentary characteristics of the continental slope, and the detrital zircon U-Pb age spectrum showed a significant northern paleo Pearl River source signal, indicating that the western source area had gradually weakened during the early Miocene, and the northern paleo Pearl River source mainly provided debris supply for the Baiyun sag.